2010
DOI: 10.1152/ajpregu.00526.2009
|View full text |Cite
|
Sign up to set email alerts
|

Renal NOS activity, expression, and localization in male and female spontaneously hypertensive rats

Abstract: Sullivan JC, Pardieck JL, Hyndman KA, Pollock JS. Renal NOS activity, expression, and localization in male and female spontaneously hypertensive rats. Am J Physiol Regul Integr Comp Physiol 298: R61-R69, 2010. First published November 4, 2009 doi:10.1152/ajpregu.00526.2009.-The goal of this study was to examine the status of the renal nitric oxide (NO) system by determining NO synthase (NOS) isoform activity and expression within the three regions of the kidney in 14-wk-old male and female spontaneously hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 55 publications
10
65
0
Order By: Relevance
“…Female sex hormones consistently increase NO production in vitro (32), although in vivo studies have yielded conflicting results (11). Consistent with our current results, we have previously published that manipulation of female sex hormones in SHR does not alter NOS enzymatic activity or expression in the renal IM (45) or cortex (44). In agreement with our results, OVX in Sprague-Dawley rats (33), DS rats (on 0.1% NaCl) (22), or Fischer-344 rats (37) does not alter renal NOS expression.…”
Section: Intact Ns Intact Hs Ovx Ns Ovx Hssupporting
confidence: 90%
See 1 more Smart Citation
“…Female sex hormones consistently increase NO production in vitro (32), although in vivo studies have yielded conflicting results (11). Consistent with our current results, we have previously published that manipulation of female sex hormones in SHR does not alter NOS enzymatic activity or expression in the renal IM (45) or cortex (44). In agreement with our results, OVX in Sprague-Dawley rats (33), DS rats (on 0.1% NaCl) (22), or Fischer-344 rats (37) does not alter renal NOS expression.…”
Section: Intact Ns Intact Hs Ovx Ns Ovx Hssupporting
confidence: 90%
“…We previously reported that female SHR have greater renal inner medullary NOS activity and NOS1 protein expression than males, and female SHR are more dependent on NOS to maintain their BP than males (2,45). Relative to SHR, DS rats have been suggested to be an NO-deficient rat strain (1,4,59), although few studies have directly compared NOS in the two strains.…”
Section: Intact Ns Intact Hs Ovx Ns Ovx Hsmentioning
confidence: 99%
“…Future studies will directly address this question. ANG II stimulation of NADPH oxidase has been shown to reduce nitric oxide (NO) bioavailability in kidneys of male SHR (2), and we have previously published that female SHR have greater NO bioavailability in the renal cortex than male SHR, independent of alterations in NO synthase activity or expression (48). We proposed that greater NO bioavailability in females was the result of less scavenging of NO by O 2 ·Ϫ (50); therefore, we hypothesize that enhanced NO bioavailability may mitigate ANG II-induced increases in blood pressure (BP) to a greater extent in female SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated CDs were immediately processed for Western blotting or incubated with Hank’s Balanced Salt solution + 250 μM L-arginine + 200U/ml superoxide dismutase for 1 h for nitrite measurements. Western blots were performed as previously described 6 , and antibodies are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%